(3GdYbO GdefXe ddMcGe ajeG jLQi Hjfge ef GdYbhO hGdCMcGes - (3CHh GdbGSe Sdehf Hf Ydj Hf Sdehf GdcfGfj,J (B767 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3cPG hQVjg hGdbi efg hTgO YdjgeG HPdc ai cPG HjGf EPG OYG GdeHJGY s
(3BNQgG (B:s
(3bGd GHf QTO hgPG eGdG ENJdGa ajg GYdeg ai GdejJ hCeG ai GdJadjS aajg s
(3HgG fXGe GdJYbjHIs
(3fSNI YdjgG eWGdYI hJUhjHGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B114 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B643s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B111s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs